Analysis of type 2 diabetes and obesity genetic variants in Mexican Pima Indians: Marked allelic differentiation among Amerindians at HLA. (17th May 2018) - Hsueh, Wen‐Chi; Bennett, Peter H; Esparza‐Romero, Julian; Urquidez‐Romero, Rene; Valencia, Mauro E; Ravussin, Eric; Williams, Robert C; Knowler, William C; Baier, Leslie J; Schulz, Leslie O; Hanson, Robert L
Abstract: Prevalence of diabetes and obesity in Mexican Pima Indians is low, while prevalence in US Pima Indians is high. Although lifestyle likely accounts for much of the difference, the role of genetic factors is not well explored. To examine this, we genotyped 359 single nucleotide polymorphisms, including established type 2 diabetes and obesity variants from genome‐wide association studies (GWAS) and 96 random markers, in 342 Mexican Pimas. A multimarker risk score of obesity variants was associated with body mass index (BMI; β = 0.81 kg/m 2 per SD, P = 0.0066). The mean value of the score was lower in Mexican Pimas than in US Pimas ( P = 4.3 × 10 −11 ), and differences in allele frequencies at established loci could account for approximately 7% of the population difference in BMI; however, the difference in risk scores was consistent with evolutionary neutrality given genetic distance. To identify loci potentially under recent natural selection, allele frequencies at 283 variants were compared between US and Mexican Pimas, accounting for genetic distance. The largest differences were seen at HLA markers (e.g., rs9271720, difference = 0.75, P = 8.7 × 10 –9 ); genetic distances at HLA were greater than at random markers ( P = 1.6 × 10 –46 ). Analyses of GWAS data in 937 US Pimas also showed sharing of alleles identical by descent at HLA that exceeds its genomic expectation ( P = 7.0 × 10 –10 ). These results suggest that, in addition to the widely recognized balancing selection at HLA, recent directional selection may also occur, resulting in marked allelic differentiation between closely related populations.